The Experiences of Mothers in a Neonatal Unit and Their Use of the Babble App. (June 2021) - Gibson, Charlotte; Ross, Kirsty; Williams, Matt; de Vries, Nathalie
To better understand the experiences of mothers with an infant admitted to a neonatal unit and ascertain their perspectives on an available information support app, Babble, eight mothers with an infant admitted to a Level II+ neonatal unit were interviewed. Thematic analysis was utilized and responses indicated that mothers of neonates experienced challenges around adapting to the maternal role and managing their expectations of motherhood. Relationships with staff were seen as pivotal in the development of maternal confidence and essential to the overall experience. Mothers prioritized informational support, but how mothers sought out this information depended on their individual needs. Mothers who reported using the Babble app found it to be a helpful supplementary resource, tailorable to their situation. Results suggest that greater staff awareness of parental perspectives and the development of adaptable and diverse resources, ensuring parents are provided with individualized and appropriate care, is needed.